2020
DOI: 10.3389/fbioe.2020.00725
|View full text |Cite
|
Sign up to set email alerts
|

Human Microphysiological Models of Intestinal Tissue and Gut Microbiome

Abstract: The gastrointestinal (GI) tract is a complex system responsible for nutrient absorption, digestion, secretion, and elimination of waste products that also hosts immune surveillance, the intestinal microbiome, and interfaces with the nervous system. Traditional in vitro systems cannot harness the architectural and functional complexity of the GI tract. Recent advances in organoid engineering, microfluidic organs-on-a-chip technology, and microfabrication allows us to create better in vitro models of human organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 182 publications
(235 reference statements)
0
30
0
Order By: Relevance
“…The results obtained do not apparently favor one of the two in vitro models and it can be concluded that both model systems can be equally well used to study human intestinal epithelial responses, thus selection may depend on the endpoint of interest. For instance, to derive uptake rates for pharmacokinetic modelling the robust and routinely used Transwell models might be the preferred approach 54 , while to emulate complex interactions in the intestine organ-on-chip models might be the preferred model [55][56][57] . It should be kept in mind that some specific gene functions are differently modulated in each model.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained do not apparently favor one of the two in vitro models and it can be concluded that both model systems can be equally well used to study human intestinal epithelial responses, thus selection may depend on the endpoint of interest. For instance, to derive uptake rates for pharmacokinetic modelling the robust and routinely used Transwell models might be the preferred approach 54 , while to emulate complex interactions in the intestine organ-on-chip models might be the preferred model [55][56][57] . It should be kept in mind that some specific gene functions are differently modulated in each model.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies suggest that the inclusion of bacteria may enhance differentiation and thus resemblance to the in vivo tissue. However, several technical difficulties like sustained co-culture and culture of anaerobic bacteria in an anaerobic environment need to be addressed [ 67 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…This calling for research efforts will not only involve the investigation on the impact of excipients on dissolution and permeation, but also encourage the development of PBPK modeling approaches to link these in vitro characteristics to in vivo BE simulation, e.g., generating model integrated evidence for generic drug development and assessment (64). As previously mentioned, the recently developed gut microphysiological systems may better mimic the physiological expression of metabolizing enzymes, uptake and efflux transporters in the gut (36)(37)(38)65). Therefore, further studies using these microphysiological systems would help on investigating the intestinal permeability of BCS III drugs as well as the performance of drug delivery systems in a (patho)physiologically-relevant in vitro environment.…”
Section: Research Call To Close Scientific Gapsmentioning
confidence: 99%
“…As previously mentioned, the recently developed gut microphysiological systems may better mimic the physiological expression of metabolizing enzymes, uptake and efflux transporters in the gut (Kasendra et al, 2018(Kasendra et al, , 2020Steinway et al, 2020;Workman et al, 2018). Therefore, further studies using these microphysiological systems would help in investigating the intestinal permeability of BCS III drugs as well as the performance of drug delivery systems in a (patho)physiologically relevant in vitro environment.…”
Section: Research Call To Close Scientific Gapsmentioning
confidence: 99%